"Eu nao desisto fácil" : narrativas de formaçao e atividade profissional de uma professora de educaçao física - Godoi, Marcos; Darolt Rabelo, Viviani; Moreira, Evando Carlos (2018)
The goal of this study was to investigate the formation narratives and professional activity of a Physical Education teacher in the development of extracurricular projects of gymnastics and dance in the schools where she worked. We carried out a case study with a Physical Education teacher from Cuiabá-MT, Brazil, with 19-year professional experience. Among the results, we identified in her narrative the influence of her pre-professional and professional training, the entrance phase in the career, the diversification phase, questioning professional and the investment in extracurricular projects of gymnastics and dance. Apart from being a Physical Education teacher, she was an articulator of the More Education Program and a trainer in the Municipal Education Department, which denoted involvement and diversification of the teaching profession
O objetivo deste estudo foi investigar o percurso de formação e atuação profissional de uma professora de educação física no desenvolvimento de projetos extracurriculares de ginástica e de dança nas escolas onde atuou. Realizamos um estudo de caso, com uma professora de educação física de Cuiabá-MT, Brasil, com 19 anos de experiência profissional. Dentre os resultados, identificamos em sua narrativa a influência da sua formação pré-profissional e profissional; a fase de entrada na carreira; a fase da diversificação; de questionamento profissional e o investimento em projetos extracurriculares de ginástica e dança. Além de professora de educação física, ela também atuou como articuladora do programa Mais Educação e como formadora na Secretaria Municipal de Educação, o que denotou envolvimento e diversificação do exercício da docência
Keywords: Formation; Professional activity; Projects; Teacher; Physical Education; Formação^lpt; Atividade profissional; Professora; Educação Física; Profesores; Formación de profesionales; Vida profesional